Au nanoparticle sensitized ZnO nanopencil arrays for photoelectrochemical water splitting. Issue 1 (12th August 2014) - Wang, Tuo; Lv, Rui; Zhang, Peng; Li, Changjiang; Gong, Jinlong
Abstract : Au nanoparticle (NP) sensitized ZnO nanopencil arrays were synthesized on FTO substrates by aqueous chemical growth followed by photoreduction, yielding a photocurrent of ∼1.5 mA cm −2 at 1 V vs. Ag/AgCl. The enhanced photocurrent is attributed to the surface plasmon resonance effect of Au NPs and a prolonged photo-generated electron–hole pair lifetime. Abstract : This paper describes the synthesis of Au nanoparticle sensitized ZnO nanopencil arrays on F-doped SnO2 substrates by an aqueous chemical growth and subsequent photoreduction method. The Au–ZnO nanopencil arrays yield a photocurrent of ∼1.5 mA cm −2 at 1 V versus Ag/AgCl. The enhanced photocurrent is attributed to the surface plasmon resonance effect of Au nanoparticles and the prolonged lifetime of the photo-generated electron–hole pairs. The improved stability of ZnO is due to the plasmon resonance energy transfer process enabled by the Au nanoparticles, which enhances the electric field intensity in a small, well-defined location of the ZnO semiconductor.